(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted at Farming Systems Research and Development site under On-Farm Research Division, Bangladesh Agricultural Research Institute, Tangail during the period of 2019-20 and 2000-21 having eight rice-based cropping patterns viz., Mustard-Boro-T. Aman rice, Potato-Boro-T. Aman, Mustard-T. Aus-T. Aman, Lentil- Jute-T. Aman, Wheat-Jute-T. Aman, Wheat-Sesame-T. Aman, Garden pea-Boro-T. Aman and Fallow-Boro-T. Aman (as check). The treatments were replicated five times in randomized complete block design with a plot size of 8.0 m 5.0 m. Result showed that the highest rice equivalent yield (31.77 t ha-1) was obtained from Potato-Boro-T. Aman cropping pattern which was followed by Garden pea-Boro-T. Aman cropping pattern (26.42 t ha-1). The lowest rice equivalent yield (11.37 t ha-1) was obtained from Fallow-Boro-T. Aman cropping pattern. Highest gross return (Tk. 557514 ha-1 and gross margin (Tk.260964 ha-1) and production efficiency (108.43 kg ha-1day-1) was recorded from Potato-Boro-T. Aman cropping pattern. Maximum land use efficiency (86%) was observed in Wheat-Jute-T. Aman cropping pattern. Highest benefit cost ratio was recorded from Mustard (var. BARI Sarisha-14)-Boro-T. Aman and Mustard (var. BARI Sarisha-18)-T. Aus-T. Aman pattern (2.16 and 2.13). On the other hand, highest by-product yield was obtained from Potato-Boro-T. Aman rice sequence. However, the higher sustainable yield index value was recorded in Potato-Boro-T. Aman rice (97.30%), which was closely followed by Garden pea-Boro-T. Aman (95.74%) and Mustard-Boro-T. Aman (93.3 %). The more labour (537man days ha-1) intensive cropping pattern was Potato-Boro-T. Aman rice. However, the profitable and viable cropping patterns were found Mustard-Boro-T. Aman followed by Potato-Boro-T. Aman and Garden pea-Boro-T. Aman which need to be disseminated in the farmer’s fields. Bangladesh J. Agril. Res. 47(4): 463-472, December 2022